Deficiency of miR-155 in Leukemic B-Cells Results in Cell Cycle Arrest and Deregulation of MIR155HG/TP53INP1/CDKN1A/CCND1 network - Golovina, Elena; Kokavec, Juraj; Kazantsev, Dmitry; Yurikova, Oxana; Bajecny, Martin; Savvulidi, Filipp Georgijevic; Simersky, Radim; Lenobel, Rene; Tost, Jorg; Herynek, Vit; Sefc, Ludek; Sebela, Marek; et al. (Archives of medical research, 2025)
BACKGROUND: Cell cycle progression and leukemia development are tightly regulated processes in which even a small imbalance in the expression of cell cycle regulatory molecules and microRNAs (miRNAs) can lead to an increased risk of cancer/leukemia development. Here, we focus on the study of a ubiquitous, multifunctional, and oncogenic miRNA-hsa-miR-155-5p (miR-155, MIR155HG), which is overexpressed in malignancies including chronic lymphocytic leukemia (CLL). Nonetheless, the precise mechanism of how miR-155 regulates the cell cycle in leukemic cells remains the subject of extensive research. METHODS: We edited the CLL cell line MEC-1 by CRISPR/Cas9 to introduce a short deletion within the MIR155HG gene. To describe changes at the transcriptome and miRNome level in miR-155-deficient cells, we performed mRNA-seq/miRNA-seq and validated changes by qRT-PCR. Flow cytometry was used to measure cell cycle kinetics. A WST-1 assay, hemocytometer, and Annexin V/PI staining assessed cell viability and proliferation. RESULTS: The limited but phenotypically robust miR-155 modification impaired cell proliferation, cell cycle, and cell ploidy. This was accompanied by overexpression of the negative cell cycle regulator p21/CDKN1A and Cyclin D1 (CCND1). We confirmed the overexpression of canonical miR-155 targets such as PU.1, FOS, SHIP-1, TP53INP1 and revealed new potential targets (FCRL5, ISG15, and MX1). CONCLUSIONS: We demonstrate that miR-155 deficiency impairs cell proliferation, cell cycle, transcriptome, and miRNome via deregulation of the MIR155HG/TP53INP1/CDKN1A/CCND1 axis. Our CLL model is valuable for further studies to manipulate miRNA levels to revert highly aggressive leukemic cells to nearly benign or non-leukemic types.
Keywords: Gene Expression Regulation, Leukemic; MicroRNAs; B-cells; Cell Line, Tumor; Cell Proliferation; mikro RNA; miR-155; kontrolní body buněčného cyklu; Cyclin D1; Heat-Shock Proteins; regulace genové exprese u leukemie; Carrier Proteins; inhibitor p21 cyklin-dependentní kinasy; Leukemia, Lymphocytic, Chronic, B-Cell; Leukemia; lidé; Humans; Cell cycle; CRISPR/Cas9; proliferace buněk; Cell Cycle Checkpoints; nádorové buněčné linie; Cyclin-Dependent Kinase Inhibitor p21; chronická lymfatická leukemie; transportní proteiny; cyklin D1; proteiny teplotního šoku